Pengembangan Media Gambar Seri Berbasis Flipbook Untuk Menulis Narasi Pada Siswa Kelas IV SDN 9 Dungaliyo Kabupaten Gorontalo - Fadila Dai; Rusmin Husain; Wiwy Triyanty Pulukadang; Fidyawati Monoarfa; Ade Mahniar (DE FACTO : Journal Of International Multidisciplinary Science, 2026)
This study aims to develop flipbook-based serial picture media as an alternative instructional medium for narrative writing in Grade IV elementary school. The research employed Research and Development (R&D) methodology using the ADDIE model, involving 17 Grade IV students of SDN 9 Dungaliyo, Gorontalo Regency as trial subjects. Product validation was conducted by three expert validators encompassing media, language, and content experts. Aggregate validation results showed a feasibility percentage of 92.30% categorized as "Very Feasible." Practicality testing yielded a teacher response rate of 91.67% and student response rate of 86.84%, with a combined average of 89.25% categorized as "Very Practical." These findings demonstrate that the flipbook-based serial picture media developed through Canva and Heyzine Flipbook platforms is feasible and practical for implementation as an Indonesian Language instructional medium, particularly for narrative writing competency in elementary education.